2008
DOI: 10.1007/s00205-008-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Fictitious Fluid Approach and Anomalous Blow-up of the Dissipation Rate in a Two-Dimensional Model of Concentrated Suspensions

Abstract: We present a two-dimensional (2D) mathematical model of a highly concentrated suspension or a thin film of the rigid inclusions in an incompressible Newtonian fluid. Our objectives are two-fold: (i) to obtain all singular terms in the asymptotics of the overall viscous dissipation rate as the interparticle distance parameter δ tends to zero, (ii) to obtain a qualitative description of a microflow between neighboring inclusions in the suspension.Due to reduced analytical and computational complexity, 2D models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…This observation is the essence of the so-called Iterative Minimization Lemma, first introduced in [8]. Therefore, if we find an approximation of E for sufficiently small δ, we would be able to derive an asymptotics for T 2 − T 1 then.…”
Section: Proof Of Proposition 32mentioning
confidence: 88%
“…This observation is the essence of the so-called Iterative Minimization Lemma, first introduced in [8]. Therefore, if we find an approximation of E for sufficiently small δ, we would be able to derive an asymptotics for T 2 − T 1 then.…”
Section: Proof Of Proposition 32mentioning
confidence: 88%
“…Berlyand et al [43] considered fluid flow in highly concentrated strictly two-dimensional suspensions and found that in two dimensions different types of singular terms should be considered for adequate description of the divergence of the dissipation rate. In our case this complication does not arise because, although particles are arranged on a 2D plane, fluid flow between them remains three-dimensional.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of these models to describe real-life physical phenomena relies on the validity of the underlying constitutive relations. In the presence of fine-scale effects that cannot be captured using the above closures, a more accurate estimate of the effective viscosity can be obtained, e.g., using a Lagrangian particle-scale model or the discrete network approximation [3]. We envisage that the use of adaptive model refinement will make it possible to develop advanced multiscale simulation tools for disperse two-phase flows.…”
Section: Discussionmentioning
confidence: 99%